Toxicity of gold nanoparticles complicated by the co-existence multiscale plastics - Zhang, Lan; Ma, Yuyang; Wei, Zhiliang; Wang, Luyang (Frontiers in Microbiology, 2024)
Gold nanoparticles (AuNPs) have been developed as treatment materials for various diseases and shown magnificent potential. By contrast to the broad toxicological studies on the single exposure (AuNPs), how the other health risks modulate the toxicological profile of AuNPs remains to be investigated. Plastics are among the most common health risks in daily life due to the broad utilization of plastic products. Therefore, in this study, we aimed to reveal the toxicological effects induced by co-exposure of gold nanorod (AuR) and polystyrene micro-and nano-plastics (hereinafter, referred to as AuRmPS and AuRnPS, respectively) in mice. Systematic biochemical characterizations were performed to investigate the hepatotoxicity, nephrotoxicity, neurotoxicity, inflammatory responses, alterations in gut microbiota induced by co-exposure, and to analyze the toxicological phenomena from the roles of reactive oxygen species and gut-organ axis. It has been found that hepatotoxicity, nephrotoxicity, neurotoxicity, and inflammation were exacerbated in AuRnPS and AuRmPS, and gut microbiota composition was more severely altered in AuRnPS exposure. These results suggest the necessity of reducing plastics exposure in AuNPs-based therapies. Moreover, protection against the nano-sized plastic particles holds higher priority. These findings will facilitate the explorations of methods to reduce therapeutic toxicity and improve biosafety for specific treatments by referring to the orders of importance in protecting different organs.